Features оf Flora and Vegetation of the MiddleMountain Landscapes оf the Region оf the Caucasian Mineral Waters (оn the Example оf the National Park "Kislovodskiy") - V. N. Belous; A. V. Lysenko; V. A. Shalnev (Наука. Инновации. Технологии, 2023)
Introduction. The relevance of the study is due to the need to study the current state of the vegetation cover and preserve the natural complexes of the midmountain landscapes of the Stavropol Territory. The Kislovodsky National Park was studied as the most representative territory. To identify the current state of the flora and vegetation of the national park, the floristic composition and characteristic plant communities of this territory were studied. The issues of localization and landscape differentiation of mountain-steppe and mountain-forest phytocenoses of the Kislovodsky National Park were also considered.Materials and research methods. The article analyzes the results of field studies of the national park in 2018-2021. Route studies covered various elements of relief, landscape areas and plant communities of the SPNA "National Park" Kislovodsky "and its buffer zone. The study included flora and vegetation, as well as individual floristic objects of the natural complex of the park. Coenotic surveys, collection and processing of field material were carried out according to generally accepted geobotanical methods. The work is based on geobotanical descriptions of plant communities in key areas. Monitoring studies concerned the study and conservation of a rare component of the flora of protected areas.The results of the study and their discussion. Within the studied communities, we identified four enlarged variants of natural vegetation, differing in the composition of the cenoflora, dominant species, structure, and coverage of species. The phytocenoses characterized in the article reflect generalized ecotopic units associated with the ecological regime and water-physical properties of habitats. The rare component of the flora of the surveyed area is represented by at least 21 rare species that are subject to regional and federal protection. The biocenotic subsystem of the park has quite well preserved the natural gene pool. It is represented by oligodominant forests, steppe meadows, mountain-steppe forb-grass phytocenoses, woody-shrub woodlands. Groups of calcepetrophytes are developed.Conclusions. The landscapes of the national park are unique in their biotic characteristics. This is due to significant dissection, and in heat and moisture circulation - an increase in moisture and a decrease in thermal performance. In view of the formation of large areas of forest park zones, there are a large number of introduced species. At the same time, they experience a significant anthropogenic load. In the study area, the vegetation cover of landscape areas and tracts is represented by a series of representative communities of a good degree of preservation. It serves the purposes of effective protection and maintenance of a sustainable ecological balance in the main protected area. Meanwhile, the state of flora and vegetation in connection with the current pace of their "development" requires additional measures to limit economic activity and adverse anthropogenic impacts on the natural complex of protected areas. Observations have shown that due to the nature of the development of the territory (recreational load, proximity to the residential part of the resort city), the vast majority of registered rare species have difficulties in the reproductive activity of plants and low competitiveness.